Investigation of thermo-aerodynamic characteristics of banks of tubes with punched spiral finning - Galushchak, Irina; Gorbatenko, Sergey (Eastern-European Journal of Enterprise Technologies, 2017)
An application of tubes with punched spiral-tape finning is promising for heat exchange intensification in convective heating surfaces of boilers and boilers-utilizers. Results of experimental research into thermo-aerodynamic characteristics of specified heating surfaces are presented. As a result of research, heat exchange intensification by 17…32 % due to fin punching was established. Heat transfer increases at an increase in the Reynolds number and a decrease in the degree of finning. Dependence of heat transfer on the accepted parameter for characterizing the bank geometry – relative to longitudinal pitch of tubes – is extreme with peaks in domain of variability relative to longitudinal pitch of 2.7…3.5. Efficiency of punched finning was determined. Results of the study of aerodynamic resistance showed its increase by 18…40 % due to the punching of fins. Resistivity increases at an increase in reduced length of the extended surface, and decreases at an increase in ratio of transverse pitch of tubes of the bank to longitudinal pitch and in Reynolds number. Results of experiment were generalized and formulas for engineering calculations of heat exchange and aerodynamic resistance of in-line tube banks with punched spiral finning were proposed. The formulae hold in domains of variability of defining parameters: finning coefficient y=6.01…9.012, relative longitudinal pitch of tubes in banks s2=2…6, Reynolds numbers Red=6·103…4·104 and Ree=5·103…4·104, ratios of tube pitches S1/S2=0.4…2.5 and reduced length of extended surface – H/F=4.58…30.45. We established the intervals variability in ratio of pitches of tubes, in which thermo-aerodynamic efficiency of in-line and staggered tube banks is maximal, respectively: 1.0...1.5 and 2.0...3.0. Within these intervals, values of the Kirpichov criterion are, respectively, E=125...150 for in-line and 75...80 for staggered banks. Formulae establish relationship between Nusselt and Euler criterion with geometric characteristics of banks and Reynolds numbers. We determined thermo-aerodynamic efficiency of in-line and staggered banks of tubes with punched spiral finning by results of experimental studies. In-line banks have higher efficiency. As a result of calculation research into thermo-aerodynamic efficiency of four types of heating surfaces of a powerful boiler-utilizer, in-line tube banks with punched spiral finning turned out to be more efficient by this parameter. The Kirpichov criterion for these tube banks, located in one shell, is 319, for staggered tube banks with punched finning – 228.8, for staggered tube banks with continuous finning – 223.8, and for staggered bare-tube banks – 143.0.